DETERMINANTS OF BRIMO CUSTOMER SATISFACTION: ANALYSIS OF FEATURES, SECURITY, AND QUALITY OF SERVICE - Rimadani, Lianda; Suharto, Akhmad; Nursaidah, Nursaidah (Univesitas Muhammadiyah Tangerang, 2025)
This study investigates the factors influencing customer satisfaction with BRImo digital banking services, with a specific focus on feature usage, security, and service quality. The research is particularly urgent given the rapid digital transformation in Indonesia's banking sector and the lack of studies examining digital banking adoption in rural areas. Using a quantitative approach, this study collected data through questionnaires distributed to 95 BRImo users at BRI Unit Suboh Situbondo, selected through simple random sampling. Multiple regression analysis was employed to analyze the relationships between the independent variables (features, security, and service quality) and customer satisfaction. The findings reveal that service quality emerges as the most significant factor affecting customer satisfaction, while feature usage and security show no substantial impact. These results provide novel insights by highlighting the distinct dynamics of digital banking adoption in rural contexts, where service quality outweighs technological features in driving user satisfaction. The study contributes to the existing literature by offering empirical evidence from an underbanked region and challenging conventional assumptions about digital banking adoption drivers. For practitioners, the findings suggest that banks should prioritize service reliability and responsiveness when expanding digital services to rural customers, rather than focusing solely on feature-rich applications.